A new type of pyroclastic deposit on the Moon containing Fe‐spinel and chromite. Issue 17 (13th September 2013) - Yamamoto, S.; Nakamura, R.; Matsunaga, T.; Ogawa, Y.; Ishihara, Y.; Morota, T.; Hirata, N.; Ohtake, M.; Hiroi, T.; Yokota, Y.; Haruyama, J.
<x xml:space="preserve">Abstract</x> [1] We present details of the identification of sites that show an absorption band at visible wavelengths and a strong 2 μm band using the SELENE Spectral Profiler. All the sites exhibiting the visible feature are found on the regional dark mantle deposit (DMD) at Sinus Aestuum. All the instances of the visible feature show a strong 2 μm band, suggestive of Fe‐ and Cr‐rich spinels, which are different from previously detected Mg‐rich spinel. Since no visible feature is observed in other DMDs, the DMD at Sinus Aestuum is unique on the Moon. The occurrence trend of the spinels at Sinus Aestuum is also different from that of the Mg‐rich spinels, which are associated with impact structures. This may suggest that the spinel at Sinus Aestuum is a different origin from that of the Mg‐rich spinel.